2015
DOI: 10.1093/rheumatology/kev234
|View full text |Cite
|
Sign up to set email alerts
|

Specific autoantibody profiles and disease subgroups correlate with circulating micro-RNA in systemic sclerosis

Abstract: Circulating miRNA profiles differ between lcSSc and dcSSc patients and between patients with different autoantibodies. This is the first time autoantibody profiles, disease phenotypes and plasma miRNA profiles have been shown to correlate in an autoimmune disease. The data support a pathobiological role of miRNAs because specific miRNAs associate with autoantibody profiles of known diagnostic and prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…The miR-92a family regulates fundamental processes in the development of mammalian organs including heart, blood vessel formation, lungs and the immune system. Among these, miR-92a-3p acquires specific relevance lacking for other miRNAs, because decreased circulating levels have been associated with interstitial lung disease (ILD) in SSc patients [21]. However, this association was not confirmed in another study.…”
Section: Mir-92a-3p In Ipf and Ssc Fibrogenesismentioning
confidence: 92%
See 2 more Smart Citations
“…The miR-92a family regulates fundamental processes in the development of mammalian organs including heart, blood vessel formation, lungs and the immune system. Among these, miR-92a-3p acquires specific relevance lacking for other miRNAs, because decreased circulating levels have been associated with interstitial lung disease (ILD) in SSc patients [21]. However, this association was not confirmed in another study.…”
Section: Mir-92a-3p In Ipf and Ssc Fibrogenesismentioning
confidence: 92%
“…For example, miR-210, miR-17-5p, miR-155-5p and miR-101-3p show contradictory results [21,29,30,37,42,46,48,49]. Of note, opposite results have been described for miR-125a-5p and 133b-3p: both are downregulated in SSc tissues [24,37] and upregulated in IPF lungs [40,42].…”
Section: Minor Overlapping Mirnasmentioning
confidence: 96%
See 1 more Smart Citation
“…Koba et al observed different miRNA expression patterns in SSc compared to healthy controls, and that combining miR-206 and miR-21 may be more informative in distinguishing SSc patients from healthy subjects than either miRNA alone [152]. Wuttge et al examined circulating miRNA expression profiles and their correlation with disease phenotype and autoantibody status [153]. They identified 4 miRNAs (miR-223, -181b, -342-3p, -184) that were differentially expressed between diffuse SSc and limited SSc, and that 5 miRNAs (miR-409-3p, -184, -92a, -29a, -101) were differentially expressed in one or more autoantibody groups; both of which further confirmed by logistic regression and receiver operating characteristic curve analysis.…”
Section: Epigenetic Impact In Ssc Pathogenesismentioning
confidence: 99%
“…MiRNA‐223, ‐181b, ‐342‐3p and ‐184 were differentially expressed in the lSSc and dSSc groups, and miRNA‐409, ‐184, ‐92a, ‐29a and ‐101 exhibited greatly different levels in one or more autoantibody groups. Specific miRNAs were associated with autoantibody profiles of known diagnostic and prognostic value . A 21‐miRNA combined model was constructed with optimum accuracy (80%) to differentiate SSc from both normal subjects and those with lupus.…”
Section: Global Epigenetics and Sscmentioning
confidence: 99%